TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK BAGI HASIL DENGAN SISTEM BETTONAN STUDI KASUS PENGELOLAAN SAWAH - Saini Saini; Fatmawati Fatmawati; Devi Undhatuz Zulfa (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2023)
The need for humans to remain intertwined with other humans to meet their needs, which cannot be fulfilled alone, is why cooperation in the agricultural sector is held. Production sharing cooperation in the management of rice fields in Sumberpakem Village has existed for a long time. However, the implementation is still not in accordance with sharia law. The purpose of this research is to find out the practice of profit sharing with the bettonan system in terms of sharia economic law. the method used in this research uses qualitative research with descriptive qualitative research. data collection techniques use observation, interviews and documentation, with data analysis using the Milles and Hubberman method. the results of this study show that the process of managing rice fields in Suberpakem Village, Sumberjambe District, Jember Regency consists of two types, paroan and bettonan, which in Islamic law is included in the muzara'ah contract. The management of rice fields with the bettonan system is that the landowner gives his rice fields to the tenant farmers by providing seeds, fertilizers, and plowing tools, and the management process is borne by the tenant farmers, but in practice the owner of the rice fields does not determine the period of management and in the division of the results the owners of the rice fields vary in determining the division of the harvest with the bettonan system there are those who use 4: 1, 5: 1 and some set aside first then the results are divided 5: 1.